Crosstalk between hypoxia-inducible factor-1α and short-chain fatty acids in inflammatory bowel disease: key clues toward unraveling the mystery - Xiao, Jinyin; Guo, Xiajun; Wang, Zhenquan (Frontiers in Immunology, 2024)
The human intestinal tract constitutes a complex ecosystem, made up of countless gut microbiota, metabolites, and immune cells, with hypoxia being a fundamental environmental characteristic of this ecology. Under normal physiological conditions, a delicate balance exists among these complex "residents", with disruptions potentially leading to inflammatory bowel disease (IBD). The core pathology of IBD features a disrupted intestinal epithelial barrier, alongside evident immune and microecological disturbances. Central to these interconnected networks is hypoxia-inducible factor-1α (HIF-1α), which is a key regulator in gut cells for adapting to hypoxic conditions and maintaining gut homeostasis. Short-chain fatty acids (SCFAs), as pivotal gut metabolites, serve as vital mediators between the host and microbiota, and significantly influence intestinal ecosystem. Recent years have seen a surge in research on the roles and therapeutic potential of HIF-1α and SCFAs in IBD independently, yet reviews on HIF-1α-mediated SCFAs regulation of IBD under hypoxic conditions are scarce. This article summarizes evidence of the interplay and regulatory relationship between SCFAs and HIF-1α in IBD, pivotal for elucidating the disease's pathogenesis and offering promising therapeutic strategies.